A novel pathway of levodopa metabolism by commensal Bifidobacteria - M. S. Cirstea; A. Creus-Cuadros; C. Lo; A. C. Yu; A. Serapio-Palacios; S. Neilson; S. Appel-Cresswell; B. B. Finlay (Scientific Reports, 2023)
Abstract The gold-standard treatment for Parkinson’s disease is levodopa (L-DOPA), which is taken orally and absorbed intestinally. L-DOPA must reach the brain intact to exert its clinical effect; peripheral metabolism by host and microbial enzymes is a clinical management issue. The gut microbiota is altered in PD, with one consistent and unexplained observation being an increase in Bifidobacterium abundance among patients. Recently, certain Bifidobacterium species were shown to have the ability to metabolize L-tyrosine, an L-DOPA structural analog. Using both clinical cohort data and in vitro experimentation, we investigated the potential for commensal Bifidobacteria to metabolize this drug. In PD patients, Bifidobacterium abundance was positively correlated with L-DOPA dose and negatively with serum tyrosine concentration. In vitro experiments revealed that certain species, including B. bifidum, B. breve, and B. longum, were able to metabolize this drug via deamination followed by reduction to the compound 3,4-dihydroxyphenyl lactic acid (DHPLA) using existing tyrosine-metabolising genes. DHPLA appears to be a waste product generated during regeneration of NAD +. This metabolism occurs at low levels in rich medium, but is significantly upregulated in nutrient-limited minimal medium. Discovery of this novel metabolism of L-DOPA to DHPLA by a common commensal may help inform medication management in PD.